Scrotal swelling after intra-abdominal injury. (8th March 2011) - Prentice, Caroline; Schofield, Andrew
Abstract : A fit and well gentleman presented with scrotal swelling, 2 days after blunt force trauma to the lower left side of his chest. At the time of injury, a focused assessment with sonography for trauma (FAST) scan for intra-abdominal trauma was negative. He was discharged but returned with persistent pain and swelling of the scrotum 4 days after the injury. This swelling was due to a haematocele secondary to splenic laceration caused by the original trauma. He remained well and did not require further intervention; the scrotal swelling had resolved after 2 weeks. This case highlights that intra-abdominal injury is an important differential of acute scrotal swelling and that 'FAST negative' needs to be treated with caution in order not to miss more subtle injuries.